The Meaning of Nafs in the Qur’an Based on Quraish Shihab’s Interpretation - Alpaqih Andopa; H Hardivizon; Nurma Yunita (Institut Agama Islam Negeri (IAIN) Curup, 2018)
: the word nafs (soul) in the context of human speech shows a side in human that has good and bad potential. In the Qur'an, nafs is mentioned 295 times. The type of this research is librarry research, namely research through library data that is representative and relevant to the research object in the form of notes, transcripts, books, interpretation books, and Arabic language dictionaries etc. The collection of research data is obtained by collecting and analyzing data relating to the nafs and books relating to human personality data sources using primary data, secondary data, and tertiary data. The research method used in this research is the method of Maudhu'i's (thematic) of interpretation that is interpreting the Qur’an according to a particular theme or topic. The results of this study indicate that the meaning of first nafs is the power of lust anger and stomach contained in the human soul and is the source of the emergence of despicable morals. As for the second meaning, nafs is a spiritual soul that is lathif, spiritual and rabbani. This nafs in the second sense is what constitutes human rights which distinguishes from animals and other creatures. He classified the Nafs into three, those are: First, Al-Nafs al-Muthmainnah, namely: A clear and bright soul with the remembrance of Allah and eradication of the influence of lust and despicable qualities; second, al-Nafs al-Lawamah, namely the soul that regrets itself; third, al-Nafs al-Amarah, which is the soul that always commands evil.